2016
DOI: 10.1016/j.jpeds.2016.02.051
|View full text |Cite
|
Sign up to set email alerts
|

High Flow Nasal Cannula Use Is Associated with Increased Morbidity and Length of Hospitalization in Extremely Low Birth Weight Infants

Abstract: Objective To determine differences in the incidence of bronchopulmonary dysplasia (BPD) or death in extremely low birth weight infants managed on high flow nasal cannula (HFNC) vs continuous positive airway pressure (CPAP). Study design This is aretrospective data analysis from the Alere Neonatal Database for infants born between January 2008 and July 2013, weighing ≤ 1000 g at birth, and received HFNC or CPAP. Baseline demographics, clinical characteristics, and neonatal outcomes were compared between the i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
35
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 56 publications
(36 citation statements)
references
References 24 publications
1
35
0
Order By: Relevance
“…It would have been useful to measure carbon dioxide values to help ascertain the exact mechanism of the relationship with oxygenation in the “nasal washout theory”. As there are studies showing that NHF is associated with a longer length of respiratory support and oxygen duration, a greater likelihood of developing BPD or death, a delay in establishing oral feeds, increased use of postnatal steroids and prolonged hospitalization in preterm infants, it is imperative that we investigate this further.…”
Section: Discussionmentioning
confidence: 99%
“…It would have been useful to measure carbon dioxide values to help ascertain the exact mechanism of the relationship with oxygenation in the “nasal washout theory”. As there are studies showing that NHF is associated with a longer length of respiratory support and oxygen duration, a greater likelihood of developing BPD or death, a delay in establishing oral feeds, increased use of postnatal steroids and prolonged hospitalization in preterm infants, it is imperative that we investigate this further.…”
Section: Discussionmentioning
confidence: 99%
“…Several retrospective cohort studies have demonstrated a longer duration of respiratory support or supplemental oxygen therapy in very preterm infants managed with nHF compared with CPAP . The interpretation of these studies is limited by methodological considerations; there may be significant differences in the severity of lung disease and other comorbidities between the groups.…”
Section: Indications For Nhf Therapymentioning
confidence: 99%
“…21 In a retrospective study by Taha et al the use of HFNC in extremely low birth weight infants was associated with a higher risk of death or bronchopulmonary dysplasia, increased respiratory morbidities and prolonged hospitalisation. 22 Another retrospective study by Hoffman et al of PBs <33 weeks GA found the HFNC group had higher rates of retinopathy of prematurity (ROP) and received a significantly longer duration of noninvasive respiratory support. 23 The more recent HIPSTER trial demonstrated a significant difference in treatment failure at 72 h between the HFNC (25.5%) and CPAP (13.3%) groups.…”
Section: What This Paper Addsmentioning
confidence: 99%
“…In a retrospective study by Taha et al . the use of HFNC in extremely low birth weight infants was associated with a higher risk of death or bronchopulmonary dysplasia, increased respiratory morbidities and prolonged hospitalisation . Another retrospective study by Hoffman et al .…”
mentioning
confidence: 97%